ANALISIS MODEL ALTMAN, SPRINGATE, ZMIJEWSKI DAN GROVER SEBAGAI ALAT PREDIKSI FINANCIAL DISTRESS PADA PT SAMPOERNA AGRO TBK PERIODE 2019-2024. - Rahma Dewi; Rossa Andiani Putri; Wina Angriany Simanullang (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the analyze bankruptcy prediction using four financial distress models: Altman, Zmijewski, Springate, and Grover. Furthermore, it also aims to determine the significant differences between the four financial distress models. Financial distress is often defined as failure, insolvency, default, and bankruptcy to categorize a company's economic problems. The object of this study is PT Sampoerna Agro Tbk for the 2019-2024 period. This study uses a comparative descriptive quantitative approach. The data used are secondary data in the form of financial reports of PT Sampoerna Agro Tbk. Data processing is done by calculating each model using Microsoft Excel, while statistical testing is done through the Shapiro-Wilk test, homogeneity of variance test, and One-Way ANOVA test with the help of SPSS version 16 software. The results of the ANOVA test will later be the basis for drawing conclusions regarding the differences in financial distress prediction performance between the models tested. Based on the test results, it shows that there are significant differences between the four models in predicting financial distress